Utilização de Moringa em água residuária de suínos - Tavares, Renata Mendes (2012)
The pig is considered polluting due to large amount of waste generation. Therefore, it is important to implement measures of treatment or reuse of wastewater generated. The seed of Moringa can be used as an alternative for treatment of wastewater. The objective was to evaluate the treatment efficiency of swine wastewater using moringa seed. Crushed moringa seeds were added to wastewater from pig manure at doses 3.0, 4.0, 5.0, 6.0, 7.0 and 8.0 g / liter in the same dosages and added to 1.0 , 1.5, 2.0, 2.5, 3.0 and 3.5 g of hydrated lime. We measured the time of coagulation and flocculation effluent using equipment Jar-Test, pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD) and nitrogen and phosphorus from wastewater before and after the test to APHA (2005). The experimental design was completely randomized factorial or 6 x 6, using three replicates per treatment. The increased as the concentration of Moringa seeds and the dose of hydrated lime, there was an increase in clotting time. The process of coagulation / flocculation took place efficiently when the jug was added alone. In treatments containing lime, no phase separation, so there is formed supernatant. The pH increase occurred with the addition of lime, reaching the value 6.5, which is ideal for good flocculation. The average values of COD after treatment was 107 mg / l and BOD values of 78 mg / L, and concentrations of nitrogen and phosphorus. Moringa should be used alone in treating swine wastewater, as provided under times of coagulation / flocculation, pH ideal for efficient flocculation and values of COD and BOD achieved efficiency standard required by law for the discharge of effluents into bed d water.